SNAP23, Syntaxin4, and vesicle-associated membrane protein 7 (VAMP7) mediate trafficking of membrane type 1–matrix metalloproteinase (MT1-MMP) during invadopodium formation and tumor cell invasion - Williams, Karla C. (The American Society for Cell Biology, 2014)
Movement through the extracellular matrix (ECM) requires cells to degrade ECM components, primarily through the action of matrix metalloproteinases (MMPs). Membrane type 1–matrix metalloproteinase (MT1-MMP) has an essential role in matrix degradation and cell invasion and localizes to subcellular degradative structures termed invadopodia. Trafficking of MT1-MMP to invadopodia is required for the function of these structures, and here we examine the role of N-ethylmaleimide–sensitive factor–activating protein receptor (SNARE)–mediated membrane traffic in the transport of MT1-MMP to invadopodia. During invadopodium formation in MDA-MB-231 human breast cancer cells, increased association of SNAP23, Syntaxin4, and vesicle-associated membrane protein 7 (VAMP7) is detected by coimmunoprecipitation. Blocking the function of these SNAREs perturbs invadopodium-based ECM degradation and cell invasion. Increased level of SNAP23-Syntaxin4-VAMP7 interaction correlates with decreased Syntaxin4 phosphorylation. These results reveal an important role for SNARE-regulated trafficking of MT1-MMP to invadopodia during cellular invasion of ECM.